Shelf-life estimation of undermilled Pinilisa rice, an aromatic traditional rice variety - Billedo, Elyss G.; Dumelod, Benelyn D. (Quezon City College of Home Economics, University of the Philippines Diliman, 2016)
Shelf-life estimates for undermilled aromatic Pinilisa rice grains packed in two materials-woven polypropylene rice sack (WPPRS) and polyamide-polyethylene (PA-PE) laminate-were determined through storage in an accelerated environment (37°C and 100% relative humidity). Endpoint indicators such as significant decrease in aroma acceptability, increase in off-odor intensity and visible mold growth were also assessed. The shelf-life estimates at 37°C were derived via a mathematical model that considered the storage environment of the system (relative humidity and saturation vapor pressure at the storage temperature), as well as the permeability of the packaging materials, and the water activity and moisture content of the samples. The shelf-life of the grains stored in WPPRS is 92 days, whereas vacuum-packed samples in PA-PE laminate, 140 days. The critical moisture content of the product, i.e., the moisture content at which hedonic rating for aroma was 5 or lower (in a 9-point scale) for the PA-PE laminate was reached at Day 25 of accelerated storage, and the moisture content at which mold growth was observed for WPPRS, at Day 3 of storage under identical conditions. Monitoring of sensory properties as perceived by the consumer panel as well as important physico-chemical parameters (pH, Aw, color and fat acidity) indicated significant changes in the off-odor intensity, aroma acceptability, and purchase intent, with increasing storage time. Physico-chemical parameters such as moisture content, water activity, fat acidity and color of the sample were positively correlated with storage period but sample pH correlated negatively. Relative deviation of 2.18% between empirical and predicted moisture content in Pinilisa in PA-PE laminate indicated good fit and reliability of data.
Submitted June 2016.
Thesis (BS Food Technology)--University of the Philippines Diliman.
Keywords: Rice -- Philippines